Pengaruh Strategi Promosi Dan Harga Terhadap Keputusan Pembelian Yang Dimediasi Oleh Minat Beli Kain Sasirangan Bordir - Periyadi Periyadi; Junaidi Junaidi; Noorlaily Maulida (At-Tadbir : jurnal ilmiah manajemen, 2020)
The main objective of this research is to examine and analyze how much promotion strategy and price influence purchasing decisions mediated by buying interest in embroidery sasirangan fabrics. The method used in this research is quantitative research with a formal research procedure design that contains clear definitions of research objectives and information needs. To answer and achieve the research objectives, regression analysis will be used. The object of this research is the consumer or potential consumer of the Sasirangan Embroidered cloth "Bunga Bangkal Sasirangan" in the Bangkal Cempaka Village, Banjarbaru, South Kalimantan. From the research results, it is known that the promotion strategy directly affects the buying interest of Sasirangan cloth, while the price does not have a significant effect. The ability of the purchase intention variable as a mediator shows that the purchase intention variable can only mediate the effect of promotional strategies on purchasing decisionsKeywords: Promotion Strategy, Price, Purchase Decision, Buying Interest.